Assessment of Natural Radionuclide contents and Impacts in the mud soil of Ido-Ijesa, South-Western Nigeria. - SULEMAN Kamaldeen Olasunkanmi (Ladoke Akintola University of Technology, 2016)
There has been great concern about the health risks associated with exposure to natural radioactivity present in soil and building materials, which could be traceable to either natural or artificial sources. Thus in this work, the natural radionuclide contents of the mud soil of Ido-Ijesa in South West Nigeria; which is commonly used as building material were analyzed . The analysis was carried out by means gamma ray spectrometry using NaI (TI) as the detector. The radioisotopes identified in the samples of the material include those of the series headed by 238U and 232Th as well as the singly occurring radioisotope 40K. The mean activity concentrations of the radionuclides were found to be 23.39±3.20, 19.37±2.60 and 165.14±7.10 Bq/kg for 226Ra, 232Th and 40K respectively. The activity index of this material was found to be 0.24±0.03. This is less than the requirement of 1 for material used in bulk amounts. Assessment of the radiological impact was made by calculating the radium equivalent activity, external and internal hazard indices and the annual effective dose equivalent and all were found to be within acceptable limit.
Keywords: Radium; mud soil; radionuclide; hazard; dose equivalent